2012
DOI: 10.1096/fj.12-219014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sphingosine kinase 1 inhibition on blood pressure

Abstract: Accumulating evidence suggests that sphingosine kinase 1 (SphK1) plays a key role in carcinogenesis by regulating cyclooxygenase-2 (COX-2) expression. Recent clinical studies have revealed that COX-2 inhibitors cause adverse cardiovascular side effects, likely due to inhibition of prostacyclin (PGI(2)). In this work, we investigated the roles of SphK1 inhibition on blood pressure (BP). The results show that lack of SphK1 expression did not exacerbate angiotensin II (Ang II)-induced acute hypertension, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
(55 reference statements)
4
11
0
Order By: Relevance
“…Interestingly, S1P administration reverted the hypotension induced by histamine in Sphk1 2/2 mice, suggesting SPHK1 as a positive regulator of MABP. In line with this evidence, the lack of SPHK1 attenuated the elevation of BP in response to the acute (Furuya et al, 2013;Wilson et al, 2015) and chronic (Wilson et al, 2015) administration of AngII. A positive role of SPHK1 in BP homeostasis has also been shown in an animal model of potassium-induced cardiac arrest with resuscitation (Gorshkova et al, 2013).…”
Section: S1p: New Player In Bp Regulation?supporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, S1P administration reverted the hypotension induced by histamine in Sphk1 2/2 mice, suggesting SPHK1 as a positive regulator of MABP. In line with this evidence, the lack of SPHK1 attenuated the elevation of BP in response to the acute (Furuya et al, 2013;Wilson et al, 2015) and chronic (Wilson et al, 2015) administration of AngII. A positive role of SPHK1 in BP homeostasis has also been shown in an animal model of potassium-induced cardiac arrest with resuscitation (Gorshkova et al, 2013).…”
Section: S1p: New Player In Bp Regulation?supporting
confidence: 75%
“…A positive role of SPHK1 in BP homeostasis has also been shown in an animal model of potassium-induced cardiac arrest with resuscitation (Gorshkova et al, 2013). Interestingly, Furuya et al (2013) also demonstrated that the absence of Sphk2 prolonged the acute hypertension induced by AngII, suggesting that SPHK2 protects from high BP.…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 70%
See 1 more Smart Citation
“…Sphingosine kinase 1 disrupts COX-2 signaling and positively regulates microsomal PGE synthase 1 (mPGES-1) (14). Since sphingosine kinase 1 increases PGE 2 and decreases TXA 2 , it modifies platelet activity by influencing the balance between PGE 2 and TXA 2 concentration and production.…”
Section: Discussionmentioning
confidence: 99%
“…While both isoforms are expressed in platelets, sphingosine kinase 1 seems to be the most important isoform in platelets (48). Furthermore, spingosine kinase 1 is able to disrupt the cyooxygenase-2 (COX-2) signaling, thus decreasing PGI 2 and increasing thromboxane formation (14).…”
mentioning
confidence: 99%